Profile of amino acid, fatty acid, and mineral content of Tambelo (Bactronophorus sp.) from Kendari, Southeast Sulawesi - Riviani Riviani; Sri Purwaningsih; Kustiariyah Tarman (Jurnal Pengolahan Hasil Perikanan Indonesia, 2016)
Public coastal had trust natural material as medicine became one of the most important things inthe discovery of medicine latest. Papua, Belitung, and Kendari coastal communities believed that tambelo(Bactronophorus sp.) can treat various kinds of diseases like lumbago, rheumatism, cough, flu, malaria, andimprove production of the breast milk, increase appetite, and vitality of man. It was important to know whatcourse content of tambelo. Tambelo could be examined amino acids, fatty acids, and mineral contents. Thehighest essential amino acids in tambelo were leucyne, lysine, and valin of 0.57%, 0.39%, 0.36%. The highestnon essential amino acid was alanin, glutamic acid, and aspartic acid of 1.24%, 1.09%, and 0.78%. Barrierof amino acid was histidine. Fatty acid total of tambelo was 29.52%, whereas the fatty acid compositionsconsist of 10.09% saturated fatty acid (SAFA) was 14.37% monounsaturated fatty acid (MUFA) was 5.06%polyunsaturated fatty acids (PUFAs). Among them, those occuring in the highest proportions were palmaticacid (4.49%), oleic acid (5.73%), palmitoleic acid (4.96%), and Aracidic acid (1.88%). Tambelo had n6/n3ratio of 1.84. Tambelo had mineral contents as Natrium of 1144000 mg/kg, calcium of 17000 mg/kg, Kaliumof 21000 mg/kg, magnesium of 13000 mg/kg, phosphor of 1900 mg/kg, cadmium < 0.24 mg/kg, and lead<1.25 mg/kg.Keyword : amino acids, Bactronophorus sp., fatty acids, mineral contents, tambelo